Quality of Life with Late-Onset Pompe Disease: Qualitative Interviews and General Public Utility Estimation in the United Kingdom - Lena Hubig; Anna-Katrine Sussex; Alasdair MacCulloch; Derralynn Hughes; Ryan Graham; Liz Morris; Syed Raza; Andrew J. Lloyd; Amanda Sowinski; Katy Gallop (Journal of Health Economics and Outcomes Research)
**Background:** Late-onset Pompe disease (LOPD) is a rare, progressive neuromuscular condition typically characterized by weakness of skeletal muscles, including those involved in respiration and diaphragmatic dysfunction. Individuals with LOPD typically eventually require mobility and/or ventilatory support. **Objectives:** This study aimed to develop health state vignettes and estimate health state utility values for LOPD in the United Kingdom. **Methods:** Vignettes were developed for 7 health states of LOPD with states defined in terms of mobility and/or ventilatory support. Vignettes were drafted based on patient-reported outcome data from the Phase 3 PROPEL trial (NCT03729362) and supplemented by a literature review. Qualitative interviews with individuals living with LOPD and clinical experts were conducted to explore the health-related quality-of-life (HRQoL) impact of LOPD and to review the draft vignettes. Vignettes were finalized following a second round of interviews with individuals living with LOPD and used in health state valuation exercises with people of the UK population. Participants rated the health states using the EQ-5D-5L, visual analogue scale, and time trade-off interviews. **Results:** Twelve individuals living with LOPD and 2 clinical experts were interviewed. Following the interviews, 4 new statements were added regarding dependence on others, bladder control problems, balance issues/fear of falling, and frustration. One hundred interviews with a representative UK population sample were completed. Mean time trade-off utilities ranged from 0.754 (SD = 0.31) (no support) to 0.132 (SD = 0.50) (invasive ventilatory and mobility support–dependent). Similarly, EQ-5D-5L utilities ranged from 0.608 (SD = 0.12) to -0.078 (SD = 0.22). **Discussion:** The utilities obtained in the study are consistent with utilities reported in the literature (0.670-0.853 for nonsupport state). The vignette content was based on robust quantitative and qualitative evidence and captured the main HRQoL impacts of LOPD. The general public rated the health states consistently lower with increasing disease progression. There was greater uncertainty around utility estimates for the severe states, suggesting that participants found it harder to rate them. **Conclusion:** This study provides utility estimates for LOPD that can be used in economic modeling of treatments for LOPD. Our findings highlight the high disease burden of LOPD and reinforce the societal value of slowing disease progression.